2020
DOI: 10.1186/s12886-020-01427-8
|View full text |Cite
|
Sign up to set email alerts
|

Axial length change and its relationship with baseline choroidal thickness – a five-year longitudinal study in Danish adolescents: the CCC2000 eye study

Abstract: Background: Myopic eyes are longer than nonmyopic eyes and have thinner choroids. The purpose of present study was to investigate whether a thinner subfoveal choroid at 11 years of age predicted axial eye elongation and myopia during adolescence. Methods: Longitudinal, population-based observational study. Axial length was measured using an interferometric device and choroidal thickness was measured by spectral-domain optical coherence tomography. Myopia was defined as non-cycloplegic subjective spherical equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(35 reference statements)
2
12
0
Order By: Relevance
“…For example, the median 5-year increase in axial length for 714 Danish adolescents 11.5 years old was 248 μm (IQR, 225). 17 The mean 18-month increase in axial length for 101 Australia children 13.1 ± 1.4 years old was 105 ± 155 μm, 18 and the axial length growth rate of 2408 6-year-old Dutch children in a recent 3-year longitudinal study was 210 ± 80 μm/year. 19 This difference may be due to differences in genetic composition, lifestyle patterns, a more competitive educational system in East and Southeast Asian countries, 20 and higher myopia progression rates in Asian populations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, the median 5-year increase in axial length for 714 Danish adolescents 11.5 years old was 248 μm (IQR, 225). 17 The mean 18-month increase in axial length for 101 Australia children 13.1 ± 1.4 years old was 105 ± 155 μm, 18 and the axial length growth rate of 2408 6-year-old Dutch children in a recent 3-year longitudinal study was 210 ± 80 μm/year. 19 This difference may be due to differences in genetic composition, lifestyle patterns, a more competitive educational system in East and Southeast Asian countries, 20 and higher myopia progression rates in Asian populations.…”
Section: Discussionmentioning
confidence: 95%
“…Spherical equivalent (SE) was calculated as the spherical value plus half of the cylindrical value, and myopia was defined as SE ≤ −0.50 diopter (D). 17 Optical coherence tomography (OCT) images of the choroid and retina were obtained from the right eyes of students through the use of spectral-domain OCT (Spectralis; Heidelberg Engineering, Heidelberg, Germany). An enhanced depth imaging system utilizing 9-mm line scans and an eye-tracking system was used to obtain horizontal sections through the fovea.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more general issue is whether such short-term changes in axial length or choroidal thickness have predictive value for future refractive development. 22,31 At least baseline choroidal thickness does not predict future myopia 32 and it must be kept in mind that changes in choroidal thickness can also be dissociated from refractive development in experiments with chickens. [33][34][35]…”
Section: Discussionmentioning
confidence: 99%
“…We found that the myopia prevalence increased with age throughout childhood and adolescence to reach a rather stable level around the age of 30–60 years, after which the prevalence appears to decline, which is in line with other studies of white Caucasians (Mutti & Zadnik 2000; Kempen 2004; Jobke et al 2008; McCullough et al 2016; Yang et al 2018). The increase in prevalence throughout childhood and adolescence is probably caused by the continuing axially elongation of the eye in this period of life (Larsen 1971; Gordon & Donzis 1985; Fledelius et al 2014; Tideman et al 2018; Hansen et al 2020a). The subsequent decrease in prevalence in the older population is thought to be a part of the ageing process, probably caused by a decrease in the anterior chamber depth and in the refractive index of the crystalline lens with age (Hemenger et al 1995).…”
Section: Discussionmentioning
confidence: 99%